Amyand’s hernia repair with surgical mesh and appendectomy: a case report - Lozada Martinez, Ivan David (2022)
Amyand’s hernia is defined as the presence of the vermiform appendix within an inguinal hernial sac. Less than 1 % of the world medical publications on hernias address this disease, out of which very few come from Latin America and the Caribbean. This is the case of a 78-year-old male patient who experienced signs and symptoms for approximately five months. He felt a lump in the right inguinal region which progressively increased in size. Two days prior to admission to the intensive care unit, he said his pain level was 8/10. During the right inguinal approach, the hernial sac was opened, revealing parts of the right colon, cecum and appendix with edematous changes. Therefore, the patient underwent an appendectomy and repair with polypropylene mesh.